Assessment of Demographic and Personality Characteristics of Elite Dancers in Turkey - ERKUT, AYŞE OYA (My University, 2010)
Assessment of Demographic and Personality Characteristics of Elite Dancers in Turkey In this study, a descriptive method was used in order to assess the demographic and personality characteristics of athletes in dancing sports. Data collected with ACL scale were evaluated with a computer programme and subscale scores were obtained. Five subscale categories which have the highest mean scores among all, were decided as typical characteristics of the athletes. The distributions of subscale scores according to demographic variables were analyzed by Mann-Whitney U test, and Pearson correlation test. In all analysis, results were tested two-sided and level of significance was accepted as 0.05. Preponderance over others, decisiveness, high self-esteem, masculine behavior were found significantly higher in younger athletes compared to old ones. On the other hand, acceptance of psychological consultation was found to be significantly higher among old athletes.